2008
DOI: 10.1113/jphysiol.2008.152348
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury‐induced attenuation of GABAergic inhibition in spinal dorsal horn circuits is associated with down‐regulation of the chloride transporter KCC2 in rat

Abstract: Most spinal cord injury (SCI) patients suffer from chronic pain. Effective therapy for this pain is lacking, and the underlying mechanisms are poorly understood. The spinal superficial dorsal horn (SDH) contains neuronal circuits capable of modulating primary afferent information involved in pain processing. KCC2 is an isoform of the K + -Cl − cotransporter that contributes to the regulation of transmembrane anion gradient which plays a key role in shaping GABA A receptor-mediated signalling in the CNS. We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 71 publications
5
90
0
Order By: Relevance
“…These neurons exhibited transient firing in response to sustained depolarizing current ( Figure 3C). The physiological and morphological features of the postsynaptic neurons in all 18 pairs closely match those of lamina II TC neurons identified previously (7,8,24,26,30,31). The excitatory synaptic transmission from PKCγ + neurons to TC neurons was less reliable, as indicated by a relatively high rate of transmission failure (23% ± 5%; n = 18; Table 1), and exhibited short-term depression induced by repetitive APs in 100-ms intervals (paired-pulse ratio: 0.6 ± 0.2, n = 18; Figure 3A, Supplemental Figure 3, and Table 1).…”
Section: Paired Patch-clamp Recordings Identify Synaptic Connections mentioning
confidence: 49%
“…These neurons exhibited transient firing in response to sustained depolarizing current ( Figure 3C). The physiological and morphological features of the postsynaptic neurons in all 18 pairs closely match those of lamina II TC neurons identified previously (7,8,24,26,30,31). The excitatory synaptic transmission from PKCγ + neurons to TC neurons was less reliable, as indicated by a relatively high rate of transmission failure (23% ± 5%; n = 18; Table 1), and exhibited short-term depression induced by repetitive APs in 100-ms intervals (paired-pulse ratio: 0.6 ± 0.2, n = 18; Figure 3A, Supplemental Figure 3, and Table 1).…”
Section: Paired Patch-clamp Recordings Identify Synaptic Connections mentioning
confidence: 49%
“…Invetigators have speculated that the partial denervation of subicular cells in TLE, due to the loss of their pre-synaptic CA1 subfield inputs region, induces a return to an immature pattern of Cl − homeostasis. This view is supported by experimental evidence in which it was shown that following damage to afferents in the spinal cord, BDNF liberated by microglia activates trkB receptors leading to a KCC2 down-regulation and a depolarizing shift in GABAergic reversal potentials associated with pathological pain responses (Price et al, 2005;Lu et al, 2008). It has also been shown that experimentally induced interictal activity in hippocampal slices maintained in vitro, downregulates KCC2 mRNA and protein expression in CA1 pyramidal neurons, which leads to a reduced capacity for neuronal Cl − extrusion (Rivera et al, 2002(Rivera et al, , 2004Blaesse et al, 2009).…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 89%
“…Inhibitory synapses can become excitatory if the reversal potential for Cl Ϫ is shifted to a more positive potential. This can occur by downregulation of Cl Ϫ transporters, as was observed in response to spinal cord injury (Lamsa and Taira, 2003;Payne et al, 2003;Lu et al, 2008;Vinay and JeanXavier, 2008). This could be a component of the recovery response because it recapitulates an earlier developmental state (Jean-Xavier et al, 2006.…”
Section: Potential Mechanisms Underlying the Recoverymentioning
confidence: 92%